The insolvency regime of natural persons with the amendments introduced by Law n.º 9/2022, of 11th january - Letícia Marques COSTA (Revista Jurídica Portucalense, 2023)
The Law n. º 9/2022, of 11th January, which transposed Directive (EU) 2019/1023 of the European Parliament and of the Council, of 20th June, made several changes to the insolvency law, namely about the insolvency regime of natural persons, including for those who hold the status of entrepreneurs who are declared insolvent. These amendments are intended to alleviate the consequences of an insolvency that has already been declared, and to increase the efficiency of the debtor's rescue. The success of these changes will make it possible to reduce the length of the processes and make them more efficient, so that a better and faster rescue of the debtor takes place. Considering the most notable change, the shortening of the deadline for obtaining a second chance, which will be attributed to you through the discharge of your debt (the so-called fresh-start), will allow you to resume your economic life sooner than before. For this reason and considering the community relations that can be established, this legislative change also seeks to harmonize the rules that exist in the different Member States for greater legal certainty.